Twelfth Five Year Plan (2012-17) and Annual Plan 2012-13 (Proposed) (Volume-II) (Statements) Haryana State - Planning Commission (Planning Commission, 2012)
12th Five Year Plan (2012-17) and Annual Plan 2012-13 Proposed Outlay Integrated Rural Energy Programme (IREP) 12th Five Year Plan (2012-17) and Annual Plan 2012-13 Proposed Outlay Land Records 12th Five Year Plan (2012-17) and Annual Plan 2012-13 Proposed Outlay Community Development 12th Five Year Plan (2012-17) and Annual Plan 2012-13 Proposed Outlay
Planning Department Government of Haryana